2021
DOI: 10.1007/s00167-021-06773-8
|View full text |Cite
|
Sign up to set email alerts
|

Medial bicompartmental arthroplasty patients display more normal gait and improved satisfaction, compared to matched total knee arthroplasty patients

Abstract: Purpose Medial bicompartmental arthroplasty, the combination of ipsilateral medial unicompartmental and patellofemoral arthroplasty, is an alternative to total knee arthroplasty for patients with medial tibiofemoral and severe patellofemoral arthritis, when the lateral tibiofemoral compartment and anterior cruciate ligament are intact. This study reports the gait and subjective outcomes following medial bicompartmental arthroplasty. Methods Fifty-five subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, some studies have shown reduced intraoperative blood loss and thereby lower post-op blood transfusion rates in BCKA compared to TKA owing to less bone resection and soft tissue resection [17,18]. Gait analysis on a treadmill by Garner et al [19] has demonstrated an advantage of BCKA over TKA in top walking speeds and stride length as well owing to retention of the anterior cruciate ligament.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown reduced intraoperative blood loss and thereby lower post-op blood transfusion rates in BCKA compared to TKA owing to less bone resection and soft tissue resection [17,18]. Gait analysis on a treadmill by Garner et al [19] has demonstrated an advantage of BCKA over TKA in top walking speeds and stride length as well owing to retention of the anterior cruciate ligament.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was assumed that TKA tibiofemoral joint reaction force data are relevant to PKA and CPKA, or that ligament forces estimated for the native knee are transferable to a PKA implanted knee. This may not be the case as differences in gait kinetics and kinematics have been observed; for example, UKA patients have been observed to walk faster than TKA patients (Wiik et al, 2013;Jones et al, 2016;Agarwal et al, 2019), as have patients with Bi-UKA (Garner et al, 2021c) and BCA-M (Garner et al, 2021e); however, the muscle loads were not changed to account for this. While these assumptions did not prevent our data replicating known clinical trends, or from correlating with prior laboratory work, there are likely subtle impacts that may have occurred.…”
Section: Figure 13mentioning
confidence: 99%
“…CPKA allows for the preservation of a wellfunctioning, well-fixed PKA in these cases (Garner et al, 2021f), or an alternative primary procedure for the one-in-three patients with bicompartmental knee disease (Garner et al, 2019;Stoddart et al, 2021). CPKA is associated with favorable patient outcomes (Biazzo et al, 2018;Wada et al, 2020;Garner et al, 2021e;Garner et al, 2021f;Garner et al, 2021b), stability (Garner et al, 2021d), and function (Wang et al, 2018;Garner et al, 2021b;Garner et al, 2021) compared to TKA. However, it is not known how use of multiple PKAs in the same knee affects load transfer to bone.…”
Section: Introductionmentioning
confidence: 99%